Evaluation of the Skills Guidance Program for Homeless and Beggars at the Social Rehabilitation Unit of Bina Karya Pasuruan - Heny Indrayanti; Sri Roekminiati; Sri Kamariyah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to evaluate the skills guidance program for vagrants and beggars (gepeng) at the Social Rehabilitation Technical Implementation Unit (UPT) Bina Karya Pasuruan, East Java Province. Vagrancy and begging represent persistent social welfare challenges that demand systematic programmatic responses from the government. The UPT Bina Karya Pasuruan serves as a central facility providing vocational skills training, social rehabilitation, and reintegration support. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with program staff, program beneficiaries, and local government officials, supplemented by observation and documentation review. The analysis framework draws on program evaluation theory with emphasis on input, process, output, and outcome dimensions. Findings indicate that the skills guidance program has been implemented with adequate facilities and committed human resources, yet several challenges remain. These include limited duration of the training program, inadequate post-program follow-up, and insufficient coordination between the UPT and potential employers or community-based organizations. Program beneficiaries generally show improvement in vocational skills; however, sustainable reintegration into productive society requires stronger aftercare mechanisms. The study recommends strengthening inter-agency coordination, extending program duration, and establishing alumni support networks to enhance the program's long-term impact on social rehabilitation outcomes.